Local injection of BDNF producing mesenchymal stem cells increases neuronal survival and synaptic stability following ventral root avulsion - Rafaela Chitarra Rodrigues Hell; Miriam Maria Silva Costa; Alfredo Miranda Goes; Alexandre L.R. Oliveira (Neurobiology of Disease, 2009)
The present study proposed to graft mesenchymal stem cells (MSCs), which continuously produce BDNF, into the spinal cord ventral horn, after ventral root avulsion. Neurotrophin expression was naturally achieved by culturing MSCs in an undifferentiated state for at least 10 weeks. Lewis rats were subjected to unilateral avulsion of lumbar ventral roots, receiving 3×105 cells injected through the lateral funiculus. Two weeks after surgery, the animals were sacrificed and neuronal survival, astroglial reaction and synaptic inputs within the motor nucleus analyzed. The results indicated that the MSCs treatment significantly rescued avulsed motoneurons. Such neuronal survival was related to in vivo mRNA up regulation as well as expression of BDNF and GDNF. Such increase was correlated to the preservation of synaptophysin- positive nerve terminals. Thus it was proposed that when maintained undifferentiated for a period of 10 weeks, MSCs may be used as a continuous source of BDNF, positively influencing neuronal survival and synaptic plasticity.